Educação superior tecnológica brasileira: uma abordagem sobre sua evolução e um estudo de caso sobre as perspectivas de egressos no Distrito Federal - Pinto, Fernanda de Campos (2018)
The present study sought to identify the impact of the evolution of the initiatives of diversification of higher education in Brazil in the 1970s on the professional development of graduates of higher technology courses at the present time. Through qualitative, exploratory and descriptive research, the international context and the Brazilian historical context of higher education diversification policies were presented. The fundamentals of technological careers in Brazil were described from Projects 15 and 19 of the Sectoral Plan for Education and Culture from 1972 to 1974, which deals with the Gradual Implementation of Short Term Courses and the evolution of these policies in subsequent decades. The impact of public policies on the diversification of higher education in the professional development of graduates of higher education courses in the present time was evidenced by means of a case study. In it, the perspectives of the development of the professional profile of graduates of the Human Resource Management Technology course of a private institution of higher education in the Federal District were examined, in order to verify the accomplishments initially proposed in the political initiatives of 1970.